Confidence Moderates the Role of Control Beliefs in the Context of Age-Related Changes in Misinformation Susceptibility. - Auslander, Margeaux V.; Thomas, Ayanna K.; Gutchess, Angela H. (Tufts University. Tisch Library., 2020)
Background/Study Context: The present experiment investigated the role of confidence and control beliefs in susceptibility to the misinformation effect in young and older adults. Control beliefs are perceptions about one's abilities or competence and the extent to which one can influence performance outcomes. It was predicted that level of control beliefs would influence misinformation susceptibility and overall memory confidence. Methods: Fifty university students (ages 18-26) and 37 community-dwelling older adults (ages 62-86) were tested. Participants viewed a video, answered questions containing misinformation, and then completed a source-recognition test to determine whether the information presented was seen in the video, the questionnaire only, both, or neither. For each response, participants indicated their level of confidence. Results: The relationship between control beliefs and memory performance was moderated by confidence. That is, individuals with lower control beliefs made more errors as confidence decreased. Additionally, the relationship between confidence and memory performance differed by age, with greater confidence related to more errors for young adults. Conclusion: Confidence is an important factor in how control beliefs and age are related to memory errors in the misinformation effect. This may have implications for the legal system, particularly with eyewitness testimony. The confidence of an individual should be considered if the eyewitness is a younger adult.; 2017.1298960.